Patient Choice, Entry, and the Quality of Primary Care: Evidence from Swedish Reforms - Jens Dietrichson; Lina Maria Ellegård; Gustav Kjellsson (Lund University, School of Economics and Management, Department of Economics, 2018)
Policies aimed to spur quality competition among health care providers are ubiquitous, but their impact on quality is ex ante ambiguous. This study contributes to the sparse empirical literature on primary care quality by examining the heterogeneous impact of recent competition enhancing reforms in Sweden. The reforms led to substantially more entry of new providers in more exposed markets, but the effects on primary care quality in these markets were modest: we find small improvements of patients' overall satisfaction with care, but no consistently significant effects on avoidable hospitalization rates or satisfaction with access to care.
Keywords: D04; H75; I11; I18; 330; Competition; Patient choice; Primary health care; Quality